Trade Unionism in Nigeria: Challenges for the 21st Century - Ed. Adewumi, Funmi (Friedrich Ebert Foundation, 1997)
The Nigerian trade union movement has a rich tradition to protect and advance the fate of Nigerian workers and contribute to national development efforts.
Keywords: Trade unions-Nigeria-ILO collection-Nonfiction